The Indian Labour Market - Govindan Raveendran (United Nations, 2016)
This work provides an in-depth analysis of trends in labour outcomes of women in India based on employment-unemployment surveys. The publication brings out the gender differentials that exist in the employment status of women and men despite the existence of legal and policy framework for the empowerment of women in the country. The labour force participation rates (LFPRs) of women are not only less than half those of men but also declined in 2011–2012. Age, marital status, presence of children, socio-religious status, area of residence, level of education and relative affluence of households are some of the determinants of labour force participation of women and men in India.